Analysis of yogurt raw materials control using MRP method at PT. Heavenly Nutrition Indonesia - Yustiana Wardhani; Ikbal Indrawan (STIE Binaniaga, 2019)
The aim of this research is going to find out the inventory level of yogurt raw materials at PT HNI. Running MRP method is to make sure that the production process is working good which can increase the efficiency of yogurt raw materials control at PT HNI. Result of the research has indicated that the method of calculation is based on the average of the last three months period, and also based on the forecast coming from Marketing Department, though some products calculated are based on the historical periode (the previous year), nevertheless the forecast of raw materials purchase is obtained. Keywords: MRP Method